2015
DOI: 10.1159/000433542
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wind Chill Factor, Temperature and Other Meteorological Parameters on the Incidence of Bell's Palsy: Results Based on a Retrospective, 7-Year Long, Greek Population Study

Abstract: Background: The etiology of Bell's palsy (BP), the most common type of dysfunction of the facial nerve, remains unclear despite vigorous research. Data concerning the effects of meteorological factors (MFs) on its appearance are inconclusive. The aim of our study was to examine the demographics of a convenience sample of patients with BP and to determine the effects of several MFs in the recorded number of cases per month (cpm). Methods: We retrospectively reviewed 568 files of BP patients and concomitant data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 20 publications
0
15
0
2
Order By: Relevance
“…Information collected included the number of cases per month, monthly temperatures, wind speeds, and monthly wind chill factor levels. The results showed that the number of cases per month was significantly and negatively correlated with the summer months and mean monthly temperatures (p = 0.002 and < 0.000, respectively) and had a significant positive correlation with the monthly wind chill factor (p < 0.000) [82]. These results suggest that the wind chill factor, which depends on both temperature and wind speed, is a novel, reliable estimator of the overall meteorological factor derived risks that influence the probability of BP occurrence.…”
Section: Acute Cold Exposurementioning
confidence: 98%
See 1 more Smart Citation
“…Information collected included the number of cases per month, monthly temperatures, wind speeds, and monthly wind chill factor levels. The results showed that the number of cases per month was significantly and negatively correlated with the summer months and mean monthly temperatures (p = 0.002 and < 0.000, respectively) and had a significant positive correlation with the monthly wind chill factor (p < 0.000) [82]. These results suggest that the wind chill factor, which depends on both temperature and wind speed, is a novel, reliable estimator of the overall meteorological factor derived risks that influence the probability of BP occurrence.…”
Section: Acute Cold Exposurementioning
confidence: 98%
“…However, some researchers have found that BP is more frequent in warm seasons (spring and summer), with its incidence peaking in September [81] More deeply, one study evaluated the influences of meteorological factors on the incidence and onset of BP. Evidence suggests that stronger wind speed of preceding day may be related to the occurrence of Bell's palsy [82] One study retrospectively reviewed 568 files of Bell's palsy patients and concomitant data of meteorological factors. The result showed the number of cases per month was significantly and negatively was significantly and negatively correlated with the summer months and mean monthly temperatures (p = 0.002 and < 0.000, respectively) and strong positive correlation with monthly wind chill factor (p < 0.000).…”
Section: Anatomical Structurementioning
confidence: 99%
“…Another small study from Greece did not find an association between weather or rapid weather changes and risk of BP [10]. Kokotis and Katsavos [24] found no association between the risk of BP and ambient temperature, but a positive correlation with the "Wind chill factor," a measure reflecting ambient temperature and wind speed. However, these were single center studies involving smaller study populations.…”
Section: Discussionmentioning
confidence: 96%
“…Bell's palsy is most likely to represent an autoimmune reaction in response to a component of the peripheral nerve myelin, leading to demyelination of the facial nerve (Greco et al, ). This autoimmune disease can be triggered by a viral infection as well as acute cold (Jeon et al, ; Khedr et al, ; Kokotis & Katsavos, ; Wakisaka et al, ) and accounts for 60%–75% of all cases of unilateral facial paralysis (Adel, Kawthar, Amine, Youssef Souha, & Abdellatif, ). Subcutaneous fat is the primary line of defense against cold stimuli, which can release various secretory factors or adipokines that signal the immune system (Huh, Park, Ham, & Kim, ; Vielma, Klein, Levingston, & Young, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathogenesis is still unclear, a cell‐mediated autoimmune demyelination mechanism is widely accepted (Abramsky, Webb, Teitelbaum, & Arnon, ; Demirci, Demirci, Kutluhan, Koyuncuoglu, & Yurekli, ; Eryilmaz, Basal, Tosun, Kurt Omurlu, & Basak, ; Greco et al, ; Ozdemir, ). Recently, accumulating evidence from epidemiological studies has shown that the incidence of Bell's palsy is related to temperature and cold wind factors (Franzke et al, ; Kokotis & Katsavos, ; Spengos et al, ; Zhao et al, ). Specifically, the incidence of Bell's palsy was found to increase during cold days or in regions with a large diurnal temperature difference, indicating that a sharp temperature change may be one of the risk factors for facial palsy (Hsieh, Wang, & Lee, ; Khedr et al, ).…”
Section: Introductionmentioning
confidence: 99%